Nitrogen, phosphorus and potassium composition of adan rice variety cultivated on rainfed lowland in Kuala Tatau, Bintulu - Adibah Mohamad Aris. (Universiti Putra Malaysia, 2016)
Paddy cultivation in Sarawak is mainly conducted in the upland or lowland with rainfield system because of absent of effective drainage infrastructure. Among popular variety that commonly grown in Bario, Bajong, Pulut and Wangi due to aromatic smell and tastier. The traditional cultivation practiced is based on rainfed without any proper irrigation with minimal application of NPK fertilizier. The objective of this study is to determine the N, P and K availability in Adan paddy field (1 acre) planted at Kuala Tatau, Bintulu. A factorial experiment with Complete Randomized Design (CRD) was established consisting of four main blocks(8x8 m)and ± 15 m distance. Establishment of sub-blocks have been performed for sampling purposes at three different growth stages 42, 90 and 150 days after planting (DAP). Soil and plant sampling and agronomic parameters such as number of tiller and plant height was measured, analysed and statistically tested using LSD (p=0.05). Results on soil fertility has shown that the area was acidic (pH=4.95) containing 4504.11 mg/kg N, 3.56 mg/kg P, and 37.71 mg/kg K at the harvesting period. Plot 1 with the highest N content produced the highest yield of 3.33 t/acre with filled grain percentage of 83%. In summary, proper water management and effective fertilizer application was recommended to improve paddy productivity and percentage of filled grain in a long term.